Modified water glass adhesive, friction-resistant chalk and preparation method of friction-resistant chalk
By introducing lithium salts, polyvinyl alcohol and their derivatives into sodium water glass, the modified water glass adhesive is formed, and the problems of excessive bonding strength, poor powder loss performance and poor water resistance caused by existing water glass adhesives are solved, and the suitable powder loss rate and water resistance of the smart powder are achieved.
Patent Information
- Application Number
- CN202411674313.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
When used in the existing water glass adhesive, the bonding strength of molded powder is too high, the powder loss performance is poor, and the water resistance is not excellent enough. The water glass hardening speed leads to poor powder flow and prone to clogging.
By introducing lithium salts, polyvinyl alcohol and their derivatives into the sodium water glass, a modified water glass adhesive is formed, and the modulus of the water glass and the particle size of the lithium salt are adjusted to improve the fluidity of the binder, reduce the bonding strength, and improve powder loss performance.
The suitable powder drop rate of Qiao powder (8-9%) is achieved, the hygroscopicity and fluidity of the binder are improved, the powder blockage is avoided, and the use effect of Qiao powder is enhanced.
Smart Images

Figure BDA0005146654000000041 
Figure BDA0005146654000000042 
Figure BDA0005146654000000051
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of friction materials for club heads in billiard sports, and in particular to a modified water glass adhesive, friction-resistant powder and a preparation method thereof. Background Art
[0002] As a material that increases the friction between the billiard ball and the cue, billiard powder can effectively improve the stability of the shot and reduce mistakes, which is of vital importance to billiards. With the rapid popularization of billiards, the market demand for billiard powder products has also increased significantly. However, the process technology of billiard powder in my country is currently in its infancy, and the product quality is not high. The mid-to-high-end market of billiard powder is mainly imported, and the share of domestic brands is relatively small. Therefore, it is necessary to develop a high-quality billiard powder to meet market demand.
[0003] The main components of powder are quartz powder and adhesive. The adhesives currently used are mainly divided into organic adhesives and inorganic adhesives. Among them, the organic adhesive has the characteristics of high bonding strength, but the disadvantage is that it is easy to emit harmful gases during use, and the overall use effect is not healthy and environmentally friendly. Water glass inorganic adhesive is a non-toxic, odorless, low-cost environmentally friendly adhesive, and the amount of toxic and harmful gases discharged during use is small. However, water glass has poor water resistance, decreased bonding effect after long-term storage, high residual strength and other problems. When directly used for powder bonding, it will cause the molded powder to have high hardness, poor powder shedding, and short storage time. In order to improve the performance of water glass, modifiers are often used to improve the performance in a certain aspect during the production process, but the overall performance is often not ideal.
[0004] For example, patent CN109762473B discloses a chemically modified silicate adhesive and a preparation method thereof, wherein a silicate solution modified by boric anhydride or boric acid is used to prepare an adhesive having good water resistance and heat resistance. However, the adhesive prepared by this method will result in excessively high bonding strength of the molding powder, poor powder loss performance, and insufficient water resistance. In addition, due to the fast hardening speed of water glass, the powder has poor fluidity, which is prone to blockage in the screw extruder, thereby hindering production. In view of this, the present invention is proposed to solve the above technical problems. Summary of the invention
[0005] In view of the above-mentioned problems that the existing adhesives have too high adhesiveness, which will lead to too high bonding strength of the molding powder, poor powder loss performance, and insufficient water resistance, and the rapid hardening speed of water glass leads to poor powder fluidity, and easy blockage in the screw extruder, the present invention provides a modified water glass adhesive, friction-resistant powder and a preparation method thereof. The specific technical scheme is as follows:
[0006] In a first aspect, the present invention provides a modified water glass adhesive, wherein the water glass modified adhesive comprises:
[0007] Sodium water glass, lithium salt, polyvinyl alcohol and derivatives thereof, wherein the mass ratio of the sodium water glass, lithium salt, polyvinyl alcohol and derivatives thereof is 100-110:9-11:6-8.
[0008] Furthermore, the powder loss rate of the chocolate powder provided by the present invention is suitable, between 8-9wt%, and has a good use effect.
[0009] Furthermore, the modulus of the sodium water glass is 2.4-2.6.
[0010] If the modulus of water glass is too large, the fluidity is poor and the bonding strength is too high; if the modulus is too low, the fluidity is enhanced but the bonding strength is poor.
[0011] Furthermore, the mesh size of the lithium borate is less than 240 meshes; if the particle size is too large, the bonding performance will be affected.
[0012] Preferably, the mesh size of the lithium borate is 200-240 mesh.
[0013] Furthermore, the lithium salt is selected from at least one of lithium borate, lithium carbonate and lithium dihydrogen phosphate.
[0014] Furthermore, the polyvinyl alcohol and its derivatives are selected from at least one of polyvinyl alcohol (PVA) and polyvinyl alcohol and its derivative butyral (PVB).
[0015] In a second aspect, the present invention provides a kind of smart powder, comprising:
[0016] 60-70 parts of quartz powder, 10-15 parts of modified water glass, 3-5 parts of pigment and 7-12 parts of water.
[0017] Furthermore, the pigment is selected from at least one of basic copper carbonate, phenol cyanine green and anthraquinone blue.
[0018] Furthermore, the quartz powder is a combination of quartz powders of at least three particle sizes among the first particle size, the second particle size, the third particle size, the fourth particle size and the fifth particle size;
[0019] Preferably, the quartz powder is a combination of quartz powders of a first particle size, a second particle size, a third particle size, a fourth particle size, and a fifth particle size;
[0020] Further, the particle size ranges of the quartz powder of the first particle size, the second particle size, the third particle size, the fourth particle size and the fifth particle size are 4-5 μm, 6-8 μm, 10-13 μm, 15-18 μm and 20-24 μm respectively; the addition amounts of the quartz powder of the first particle size, the second particle size, the third particle size, the fourth particle size and the fifth particle size are 10-13 parts, 23-25 parts, 16-19 parts, 6-8 parts and 5-7 parts respectively;
[0021] The combination of particle size ranges can make the quartz powder flow and compact more easily during mixing and pressing, thereby improving the uniformity and density of the material.
[0022] In a third aspect, the present invention provides a method for preparing a modified water glass adhesive, comprising:
[0023] Step 1, weigh polyvinyl alcohol and its derivatives, disperse them in water, and stir to dissolve them at 50-60° C.;
[0024] Step 2, mixing the lithium salt with the sodium water glass solution, and stirring and mixing at 60-80° C.;
[0025] Step 3: Stir and mix the solutions obtained in step 1 and step 2 at room temperature to react to obtain the product.
[0026] PVA and PVB molecules are adsorbed on the surface of silica sol colloidal particles through hydrogen bonds.
[0027] Furthermore, in step 1, the concentration of the polyvinyl alcohol and its derivatives in water is 0.002-0.003 mol / L.
[0028] Furthermore, the reaction time in step 2 is as short as 30-40 minutes.
[0029] Furthermore, the stirring speed in step 2 is 800-1200 rpm.
[0030] Furthermore, in step 2, the lithium salt and sodium water glass are mixed in a mass ratio of 9-11:100-110.
[0031] Furthermore, in step 3, the mass ratio of polyvinyl alcohol and its derivatives to sodium water glass is (6-8): (100-110).
[0032] In a fourth aspect, the present invention provides a method for preparing chocolate powder, comprising:
[0033] Step 1: Take quartz powder and basic copper carbonate and stir and mix them evenly; the quartz powder includes a combination of quartz powders of at least three particle sizes among a first particle size, a second particle size, a third particle size, a fourth particle size and a fifth particle size; preferably, the quartz powder includes a combination of quartz powders of the first particle size, the second particle size, the third particle size, the fourth particle size and the fifth particle size;
[0034] Step 2: Add the modified water glass to the powder obtained in step 1 and stir to mix evenly; extrude the powder obtained after stirring to form; then heat to remove moisture and place at room temperature to obtain the powder.
[0035] Furthermore, the heating temperature in step 2 is 60-80° C. and the heating time is 6-8 hours.
[0036] The beneficial effects of the technical solution of the present invention are as follows:
[0037] (1) The present invention introduces polyvinyl alcohol and its derivatives into sodium water glass, so that the polyvinyl alcohol and its derivatives form a coating structure with the Si-O bond of the sodium water glass, and can form a hydrogen bond with water, thereby slowing down the deliquescence rate of the Si-O bond and enhancing its anti-hygroscopicity; and the polyvinyl alcohol and its derivatives can form a thin film in the gap between the powders, effectively reducing the internal friction during the extrusion process, increasing the fluidity of the powder, preventing the powder from being blocked, and facilitating the extrusion molding of the powder;
[0038] (2) The present invention introduces lithium salt into sodium water glass, so that during the drying and airing process, due to the different expansion and contraction coefficients of lithium salt and silicate, lithium salt particles cut the adhesive film formed by the water glass, causing pores and cracks, destroying the continuity of the adhesive film, reducing the bonding strength, and improving the powder shedding performance of the powder. Finally, when 200N / m 2 Under the conditions of 500 force and friction tests, the powder loss rate is within the appropriate range of 8-9%, which has a good use effect;
[0039] (3) The present invention introduces lithium salt and polyvinyl alcohol and its derivatives, Li + It can produce complexation with the ester group formed by polyvinyl alcohol and its derivatives, making the coating network formed by polyvinyl alcohol and its derivatives on the silicon-oxygen bond more continuous and the coating effect on the Si-O bond stronger;
[0040] (4) The hydroxyl groups contained in the molecular structures of sodium water glass, lithium salt, polyvinyl alcohol and its derivatives added in the present invention are easy to form hydrogen bonds and adsorb on the surface of silica sol particles, which refines the colloidal particles and increases the density of bond bridges. Lithium salt and sodium water glass can form a solid, orderly composite structure, so that the silica sol has good film-forming continuity and stability.
[0041] (5) The present invention uses sodium water glass as raw material, which has better water resistance than other types of water glass, so that the finally prepared chocolate powder has better water resistance. DETAILED DESCRIPTION
[0042] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0043] Example 1
[0044] 1. Preparation of modified water glass binder:
[0045] Step 1, weigh polyvinyl alcohol and its derivatives, place them in water, and stir them in a 60°C water bath for 10 minutes at a stirring speed of 700 rpm until they are completely dissolved;
[0046] Step 2, mix the lithium salt (below 240 mesh) with the sodium water glass solution, stir for 30 minutes in a water bath, and the stirring speed is 1000 rpm to make them fully mixed;
[0047] Step 3: Stir and mix the solutions obtained in steps 1 and 2 at room temperature to obtain the product.
[0048] Step 2: Preparation of powder materials:
[0049] Step 1: Put 6-8 μm quartz powder, 4-5 μm quartz powder, 10-13 μm quartz powder, 15-18 μm quartz powder, 20-24 μm quartz powder and pigment in a mixer and stir for 5 minutes to mix the powders evenly;
[0050] Step 2: Add the modified water glass to the powder obtained in step 1, stir with a mixer for 5 minutes until the powder and solution are evenly mixed, gradually add the stirred powder to the extruder, and after the powder is extruded and formed, place it in an oven at 80°C for 6 hours, and then place it at room temperature for 2 hours to obtain the final powder material.
[0051] In the preparation process of the modified water glass binder of Examples 1-4 and Comparative Examples 1-4, the parameter settings refer to Table 1; in the preparation process of the powder material, the parameter settings refer to Table 2;
[0052] The quartz powder particle size ratio in Table 1 is the mass ratio of quartz powder of the first particle size, the second particle size, the third particle size and the fourth particle size;
[0053] Table 1
[0054]
[0055] Table 2
[0056]
[0057]
[0058] Comparative Example 5
[0059] 1. Preparation of modified water glass:
[0060] Step 1, weigh polyvinyl alcohol and its derivatives, place them in water, and stir them in a water bath until they are completely dissolved;
[0061] Step 2, stirring and mixing the solution obtained in step 1 and the silica sol at room temperature;
[0062] Step 3, mix lithium salt (less than 240 mesh) with the above solution, stir in a water bath to make them fully mixed, and obtain;
[0063] During the preparation of the modified water glass in this comparative example, the order of adding raw materials is different from that in Example 1, and other features are the same as those in Example 1.
[0064] 2. Preparation of smart powder:
[0065] The preparation of the chocolate powder in this comparative example is the same as in Example 1.
[0066] Performance Test:
[0067] The performance of the powder prepared in the examples and comparative examples was tested, and the test results are shown in Table 3.
[0068] The powder loss performance test method is to apply 200N / m 2 After 500 friction tests, the weight ratio of powder loss is measured; the powder loss rate of the clever powder should not be too large or too small. Under this test condition, the powder loss rate after 500 frictions is between 6-9%, which has a good effect;
[0069] The anti-hygroscopicity test is carried out according to GB / T2423.3-2016 standard, and the test condition is to place it at a humidity of 85 (±5%) for 24 hours;
[0070] The blockage of powder extrusion is obtained by visually observing the extrusion of powder during the extrusion process;
[0071] The flexural strength test is carried out in accordance with the GB / T3001-2017 standard, and the flexural strength test is carried out on a universal testing machine using a three-point bending fixture;
[0072] Table 3
[0073]
[0074] As can be seen from Table 3, the powder prepared by the method of the present invention has suitable bonding strength, a powder loss rate of 8-9%, excellent powder loss performance, and excellent water resistance and mechanical properties; while in Comparative Example 1, since polyvinyl alcohol and its derivatives are not added to modify water glass, the water resistance is poor and the storage requirements are high; in Comparative Example 2, since lithium salt is not added to modify water glass, the lithium salt cannot destroy the sodium water glass adhesive film, resulting in excessive bonding strength of the powder and not easy to lose powder; in Comparative Example 3, since ordinary sodium water glass is used instead of modified water glass (that is, sodium water glass is not modified in any way), the powder bonding strength is too high, the powder loss is poor, and the water resistance is poor; in Comparative Example 4, since quartz powder with the same particle size is selected instead of the compound with different specific particle sizes used in the present invention, the surface of the obtained powder is uneven and dense, there are gaps, and it is easy to lose powder; in Comparative Example 5, since polyvinyl alcohol and its derivatives are dissolved and mixed with sodium water glass during the modification process, and then borate is added, some substances are precipitated, the strength of the obtained powder is poor, the powder loss is serious, and it is not suitable for use.
Claims
1. A modified water glass adhesive, characterized in that: The water glass modified binder comprises: Sodium water glass, lithium salt, polyvinyl alcohol and derivatives thereof, wherein the mass ratio of the sodium water glass, lithium salt, polyvinyl alcohol and derivatives thereof is 100-110:9-11:6-8.
2. The modified water glass adhesive according to claim 1, characterized in that: The lithium salt is selected from at least one of lithium borate, lithium carbonate and lithium dihydrogen phosphate.
3. The modified water glass adhesive according to claim 1, characterized in that: The polyvinyl alcohol and its derivatives are selected from at least one of polyvinyl alcohol and polyvinyl butyral.
4. The modified water glass adhesive according to claim 1, characterized in that: The modulus of the sodium water glass is 2.4-2.
6.
5. The modified water glass adhesive according to claim 1, characterized in that: The mesh number of the lithium borate is less than 240 meshes.
6. A method for preparing the modified water glass adhesive according to any one of claims 1 to 5, characterized in that: include: Step 1, weigh polyvinyl alcohol and its derivatives, disperse them in water, and stir to dissolve them at 50-60° C.; Step 2, mixing the lithium salt with the sodium water glass solution, and stirring and mixing at 60-80° C.; Step 3: Stir and mix the solutions obtained in step 1 and step 2 at room temperature to react to obtain the product.
7. A kind of chocolate powder, characterized in that: include: 60-70 parts of quartz powder, 10-15 parts of the modified water glass according to any one of claims 1-5, 3-5 parts of pigment and 7-12 parts of water.
8. The chocolate powder according to claim 7, characterized in that The pigment is selected from at least one of basic copper carbonate, phenol cyanine green and anthraquinone blue.
9. The chocolate powder according to claim 7, characterized in that The quartz powder comprises a combination of quartz powders of a first particle size, a second particle size, a third particle size, a fourth particle size, and a fifth particle size; The particle size ranges of the quartz powder of the first particle size, the second particle size, the third particle size, the fourth particle size and the fifth particle size are 4-5 μm, 6-8 μm, 10-13 μm, 15-18 μm and 20-24 μm respectively; The added amounts of quartz powder of the first particle size, the second particle size, the third particle size, the fourth particle size and the fifth particle size are 10-13 parts, 23-25 parts, 16-19 parts, 6-8 parts and 5-7 parts respectively.
10. A method for preparing chocolate powder according to claim 7, characterized in that: include: Step 1: Take quartz powder and basic copper carbonate and stir and mix them evenly; Step 2: Add the modified water glass to the powder obtained in step 1 and stir to mix evenly; extrude the powder obtained after stirring to form; then heat to remove moisture and place at room temperature to obtain the product.
Citation Information
Patent Citations
A chemically modified silicate adhesive and its preparation method
CN109762473B